(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article examines the specific features of developing information and communication technology (ICT) skills among primary school students, the role of the teacher, and innovative approaches in the learning process. It analyzes issues related to improving students’ digital literacy, independent thinking, and the overall quality of education through the use of ICT.